CONTRIBUTION OF MOTIVATION TOWARD LEARNER AUTONOMY FOR NON-ENGLISH MAJOR STUDENTS IN LEARNING ENGLISH - Samsul Amri; Muhammad Fikri (INOVISH JOURNAL, 2019)
The aim purpose of this research was to determine how the contribution of students’ motivation toward learner autonomy for non-English major students of the Islamic University of Indragiri. It was correlational research. Population and Sample in this research were 34 students, which were selected by total sampling technique. They are second-semester students of Accounting Major of the Islamic University of Indragiri. Data collecting technique used the questionnaire in the two variables. Then the research results show that the value of students motivation is 81.62, which covered the indicators of Anxiety (81.87%), Interest (80.16%), Teacher (82.55%). Those are categorized as a strong/high category. Then the result of learner autonomy 80.18, that included Learner Strategy (79.12%), Meta-Cognitive (81.33%), Learner Attitude (80.16%). Those are also classified as a strong/high category. Moreover, the result of correlation both of variables is robserved 0.838, which is categorized as very high correlation, and r table (1%=0.349 and 5%=0.449). Thus, robserved > rtable. It means that Ho is Rejected and Ha is Accepted. In other words, there is a positive correlation between motivation and learner autonomy for non-English major students. From the analysis of the determination coefficient, it obviously found that motivation contributes positively to learner autonomy as much as 70.22%, and the others percent (29.78%) is determined by other aspects. It implies that the higher the students have motivation in learning English, the better they will have learning autonomy.